Tympanic, Infrared Skin, and Temporal Artery Scan Thermometers Compared with Rectal Measurement in Children: A Real-Life Assessment - Karel Allegaert, MD, PhD; Kristina Casteels, MD, PhD; Ilse van Gorp, RN; Guy Bogaert, MD, PhD (Elsevier, 2014)
Introduction: Body temperature measurement in children is of clinical relevance. Although rectal measurement is the gold standard, less invasive tools have become available. We aimed to describe the accuracy of tympanic, infrared skin, or temporal artery scan thermometers compared with rectal measurement to reflect core temperature. Methods: Rectal (Filac 3000; Covidien, Mechelen, Belgium), tympanic (AccuSystem Genius2 Typmanic Infrared Ear Thermometer, Covidien, Mechelen, Belgium), temporal artery scan (Exergen, Exergen Corp, Watertown, Massachusetts), and infrared (ThermoFlash Contactless Medical Electronic Thermometer, Visiomedlab, Paris, France) body temperature measurements were randomly performed and readings were collected once. Temperature readings were described as median and range, and observations were compared with rectal temperature readings (using Wilcoxon, Bland-Altman, sensitivity, and specificity tests). The child's comfort was assessed by the child, parent, and nurse (using Likert scales) and ease of use was assessed by nurses (using visual analog scale). Results: Based on observations in 294 (median age = 3.2 years, range = 0.02-17 years) children, the mean difference was 0.49°C (tympanic scan; P < 0.0001), 0.34°C (infrared skin scan; P < 0.0001), and 0°C (temporal artery scan; P = 0.9288), respectively, when compared with rectal temperature readings. Based on visual inspection of Bland-Altman plots, all tools overestimated the temperature at lower body temperature and underestimated the temperature at higher body temperature, resulting in a sensitivity of 22% to 41% and a specificity of 98% to 100% for rectal temperatures above 38°C. The Likert scale scores and the visual analog scale scores for rectal measurement were only slightly higher when compared with the other methods. Conclusions: All noninvasive techniques underperformed compared with rectal measurement. The temporal artery scan deviations were smallest, but all noninvasive techniques overestimate lower temperatures and underestimate higher temperatures compared with rectal measurement. In our hands, temporal artery scan measurement seems to be second best, but not yet ideal.